Academic procrastination and anxiety in university students of Madre de Dios - Estrada Araoz, Edwin Gustavo (2020)
The objective of this research was to determine the relationship that exists between academic procrastination and anxiety in the students of the Professional Career of Education of the National Amazonian University of Madre de Dios. The research focus was quantitative, non-experimental design and correlational type. The sample was made up of 220 students to whom the Academic Procrastination Scale and the Zung Anxiety Self-Assessment Scale were applied, instruments with the required validity and reliability. The results indicate that 48.2% of the students present a high level of academic procrastination, 39% have a moderate level of anxiety and it was statistically determined that there is a direct and significant relationship between academic procrastination and anxiety (rs = 0.359; p = 0.000 <0.05). It was concluded that the more students procrastinate, their anxiety levels will be higher.